Morphology and phylogeny of a new polychaete, Prionospio expansa (Annelida: Spionidae) from the intertidal zone of the Yellow Sea, Korea - Lee, Geon Hyeok; Lee, Ha-Eun; Min, Gi-Sik (European Journal of Taxonomy, 2023)
A new spionid polychaete, Prionospio expansa sp. nov., collected from the intertidal habitat of the Yellow Sea in Korea, is described. The new species is closely related to P. japonica Okuda, 1935 from Northeast Asia both morphologically and genetically. They share four pairs of branchiae which are cirriform and apinnate, whereas the new species differs from P. japonica in the length of the branchiae, expansion of the anteriormost body, and size of the first notopodial postchaetal lamellae. Herein, a detailed description and illustrations of P. expansa sp. nov. are provided, with molecular data for three gene fragments: mitochondrial cytochrome c oxidase subunit I, 16S ribosomal DNA (rDNA), and nuclear 18S rDNA. A phylogenetic analysis was conducted based on mitochondrial and nuclear gene fragments.